2019
DOI: 10.1017/s0007114519001193
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of essential elements chromium, manganese, iron, zinc and selenium in spot samples, first-morning voids and 24-h collections from healthy adult men

Abstract: Evaluation of Cr, Mn, Fe, Zn and Se in humans is challenged by the potentially high within-individual variability of these elements in biological specimens, which are poorly characterised. This study aimed to evaluate their within-day, between-day and between-month variability in spot samples, first-morning voids and 24-h collections. A total of 529 spot urine samples (including eighty-eight first-morning voids and 24-h collections) were collected from eleven Chinese adult men on days 0, 1, 2, 3, 4, 30, 60 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Substantial studies have also reported considerable high within-individual variabilities in sperm quality parameters [12][13][14][15] and Se concentrations in urine samples. 10,11 All these findings emphasize the importance of collecting repeated samples in the future studies.…”
Section: Interpretation In Light Of Other Evidencementioning
confidence: 86%
See 1 more Smart Citation
“…Substantial studies have also reported considerable high within-individual variabilities in sperm quality parameters [12][13][14][15] and Se concentrations in urine samples. 10,11 All these findings emphasize the importance of collecting repeated samples in the future studies.…”
Section: Interpretation In Light Of Other Evidencementioning
confidence: 86%
“…Meanwhile, a lack of association between Se status and human semen quality was also reported. 8,9 These previous studies mostly relied on a single measurement of Se concentrations and semen quality, which is prone to measurement error, given the considerable high within-individual variabilities in urinary Se concentrations 10,11 and sperm quality parameters. [12][13][14][15] More importantly, little is known about the mechanisms underlying the associations between Se status and semen quality, which are critical to improve insights for disease development and prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Because the collection of blood samples is invasive, the reproducibility of whole blood selenium measurement has rarely been studied. A longitudinal analysis of urine samples collected from 11 Chinese men at days 0, 1, 2, 3, 4, 30, 60, and 90 suggested poor reproducibility of urinary selenium (ICC = 0.03) ( 84 ). The reproducibility of whole blood and urinary selenium measurements may be affected by the kinetics of selenium absorption, distribution, metabolism, and elimination ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PG sheet moved in the direction of the sunlight and had a short response time, which was mainly related to its strong diamagnetic performance. Abnormal diamagnetic materials such as bismuth [29] and graphite [30] have larger magnetic susceptibility (χ) (up to 10 −4 -10 −3 ), and change rapidly with the increase of temperature. This made temperature a factor that can be used to manipulate the movement of PG sheet in a magnetic field.…”
Section: Photothermal Performance Of Gnta/pdms Compositesmentioning
confidence: 99%